Sweet syndrome associated with moderate leukocyte adhesion deficiency type I: a case report and review of the literature - Saito, Yoshine; Kewalramani, Anupama; Peng, Xiao P.; Magnarelli, Aimee; Lederman, Howard M. (Frontiers in Immunology, 2024)
Sweet syndrome is an acute febrile neutrophilic dermatosis characterized by the infiltration of neutrophils into the skin. It may occur idiopathically or be linked to malignancies, inflammatory or autoimmune diseases. Leukocyte adhesion deficiency type I (LAD-I) is an inborn error immunity wherein leukocytes lack adhesion molecules necessary for migration to infection sites due to mutations in the CD18 gene encoding β2 integrins. We present a case of a 16-month-old female initially diagnosed and treated for Sweet syndrome based on histopathological findings with recurrent flare episodes. Subsequent workup revealed LAD-I, making this case the first documented association between Sweet syndrome and LAD-I. Moreover, we reviewed the pertinent literatures detailing the concurrence of neutrophilic dermatosis and immunodeficiency disorders. This case underscores the significance of comprehensive evaluation for Sweet syndrome patients who are refractory to conventional treatments.